Catalogue of bias: observer bias. Issue 1 (24th January 2018) - Mahtani, Kamal; Spencer, Elizabeth A; Brassey, Jon; Heneghan, Carl
Abstract : This article is part of a series featured from the Catalogue of Bias introduced in this volume of BMJ Evidence-Based Medicine that describes biases and outlines their potential impact in research studies. Observer bias is systematic discrepancy from the truth during the process of observing and recording information for a study. Many healthcare observations are at risk of this bias. Evidence shows that treatment effect estimates can be exaggerated by a third to two-thirds in the presence of observer bias in outcome assessment. Preventing observer bias involves proper masking in intervention studies including the use of matched placebo interventions where appropriate and training of observers to make assessment consistent and reduce biases resulting from conscious or unconscious prejudices. Where observers are involved in a research study, it is probably not possible for the study to be entirely free of observer biases.